Empowerment of Communication Parents and Educators to Success Program Play Groups - Suranto Suranto; Ida Ayu Hani Erlina; Yuspik Yuspik; Yosi Melda Sari (Journal on Education, 2023)
Communication between educational institutions and parents is needed so that children's education becomes optimal. This research was conducted with the aim to explore information related to the effectiveness of communication between parents and educators in Early Childhood Education institutions. This research is a type of case study research with qualitative methods. The research subjects involved included educators, parents and managers. Data were collected using observation, interview, and documentation techniques. The results showed that the process of communication between parents and educators in early childhood education institutions was more likely to use a pattern of openness so as to enable all interested parties to exchange information. Program activities are carried out and communicated through meetings involving parents. The effectiveness of existing communication is demonstrated by the change that is getting better in the achievement and success of the Play Group program.